2013
DOI: 10.1111/1467-8551.12032
|View full text |Cite
|
Sign up to set email alerts
|

The Snowballing Penalty Effect: Multiple Disadvantage and Pay

Abstract: This paper makes the case that the current single-axis approach to the diagnosis and remedy of pay discrimination is inadequate in the case of multiple disadvantage. While a good deal is known about pay gaps, particularly those affecting women, less is known about those affecting people in other disadvantaged groups and those in more than one such group. This analysis of multiple years of pay data, n = 513,000, from a large UK-based company shows that people with more than one disadvantaged identity suffer a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
50
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 39 publications
3
50
0
Order By: Relevance
“…Rather less is known about the pay deficits experienced by people in more than one disadvantaged category, that is, those who are in dual, triple, or even quadruple axis categories (Browne & Misra, ). Recent research on multiple‐disadvantaged identity and pay (Woodhams et al, ) indicates that the more labor market disadvantages (i.e., in relation to gender, ethnicity, disability, and age) an employee has, the lower their pay is on average; in this study, the gap in median earnings was over £8,000 ($13,000) per year between the most advantaged and disadvantaged groups. These authors found that the effect of accumulation of disadvantaged identities on pay was in many cases greater than would arise from simply adding the pay penalties arising from single identities, and this effect tended to be more marked among multiple‐disadvantaged identity groups.…”
Section: Multiple Disadvantage Pay Gaps and Wage Growthmentioning
confidence: 49%
See 4 more Smart Citations
“…Rather less is known about the pay deficits experienced by people in more than one disadvantaged category, that is, those who are in dual, triple, or even quadruple axis categories (Browne & Misra, ). Recent research on multiple‐disadvantaged identity and pay (Woodhams et al, ) indicates that the more labor market disadvantages (i.e., in relation to gender, ethnicity, disability, and age) an employee has, the lower their pay is on average; in this study, the gap in median earnings was over £8,000 ($13,000) per year between the most advantaged and disadvantaged groups. These authors found that the effect of accumulation of disadvantaged identities on pay was in many cases greater than would arise from simply adding the pay penalties arising from single identities, and this effect tended to be more marked among multiple‐disadvantaged identity groups.…”
Section: Multiple Disadvantage Pay Gaps and Wage Growthmentioning
confidence: 49%
“…Our interest here is in how this might affect employees who have identities that combine more than one employment disadvantage (in relation to age, gender, ethnicity, and disability). In relation to pay levels, as opposed to pay growth, recent research (Woodhams et al, ) suggests that there may be an interaction effect that in some cases reduces average pay below what one would expect from simply adding up the pay deficits that people experience from being in a single‐disadvantaged identity category. Why this should be is not clear, and there are likely to be complex and multiple reasons.…”
Section: Multiple Disadvantage Pay Gaps and Wage Growthmentioning
confidence: 99%
See 3 more Smart Citations